2008
DOI: 10.1002/cncr.23556
|View full text |Cite
|
Sign up to set email alerts
|

Serum fucosylation changes in oral cancer and oral precancerous conditions

Abstract: BACKGROUND. The objective of the current study was to investigate the clinical usefulness of serum fucose, fucosylated glycoproteins (fucoproteins), fucosyltransferase (FucT), and α‐L‐fucosidase in oral carcinoma. METHODS. Blood samples were collected from 130 patients with untreated oral cancer (OC), from 75 patients with oral precancerous conditions (OPC), and from 100 healthy controls. Cancer patients were followed after the initiation of anticancer treatments, and 75 follow‐up samples were also collected. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 31 publications
4
58
0
Order By: Relevance
“…Most of them belonged to 41-50 year age-group (36%), followed by 61-70 year age-group (34%). This finding was consistent with that of a study from Gujarat done by Shah et al, who reported that out of 130 patients of oral carcinoma, 94% were men, with a male to female ratio of 15.7:1 [15]. These high incidences of HNCs in males are mostly attributed to smoking in urban population and tobacco chewing and snuffing in rural India.…”
Section: Wwwjcdrnet Arunava Kali Et Al Significance Of Serum L-fusupporting
confidence: 92%
“…Most of them belonged to 41-50 year age-group (36%), followed by 61-70 year age-group (34%). This finding was consistent with that of a study from Gujarat done by Shah et al, who reported that out of 130 patients of oral carcinoma, 94% were men, with a male to female ratio of 15.7:1 [15]. These high incidences of HNCs in males are mostly attributed to smoking in urban population and tobacco chewing and snuffing in rural India.…”
Section: Wwwjcdrnet Arunava Kali Et Al Significance Of Serum L-fusupporting
confidence: 92%
“…A subgroup of the cysts, including several IPMN, was observed here to contain hyperfucosylated N-linked glycans. Increased fucosylation has continued to be implicated in the progression of cancer (13)(14)(15)(16), including specifically pancreatic cancer (16,17). As such, hyperfucosylated N-glycans and glycoproteins have been targeted for quantitative label-free bottom-up glycoproteomic analysis.…”
mentioning
confidence: 99%
“…In this study, it was observed that TF, LAF and FF significantly increased in smoker groups. There is indirect evidence which indicate that, increased glycoprotein components levels are offset by increased fucosidase activity which is responsible for breaking down tissue and serum glycoproteins 31 .It is an important enzyme for fucose catabolism which is responsible for the altered fucosylation status of glycoproteins 33 . In the present study the activity of fucosidase may be altered by tobacco and smoke chemical components.…”
Section: Resultsmentioning
confidence: 99%